Effect of Hemin on the Synthesis of Hemoglobin and Other Proteins in Mammalian Cells - Beuzard, Yves (1973)
The initiation of globin synthesis in intact reticulocytes and in reticulocyte lysates is maintained by the addition of hemin. The specificity of this effect has been studied to determine whether it is restricted to hemoglobin and erythroid cells. In intact reticulocytes, hemin (500 μM) enhances the synthesis of carbonic anhydrase as well as of hemoglobin. Similar enhancement of protein synthesis is observed on addition of hemin (500 μM) to intact Krebs II ascites tumor cells, in cell-free extracts of these cells, added hemin (50 μM) increases endogenous protein synthesis and the translation of exogenous rabbit globin messenger RNA. These results provide evidence that the effect of hemin is not restricted to globin, and they suggest that hemin may enhance protein synthesis in at least some nonerythroid cells.